Associations between psoriatic arthritis and mental health among patients with psoriasis: A replication and extension study using the British Association of Dermatologists Biologics and Immunomodulators Register (BADBIR) - Georgia Lada; Hector Chinoy; Peter S. Talbot; Richard B. Warren; C. Elise Kleyn; the BADBIR Study Group (Wiley, 2022)
Abstract Background Despite some evidence that psoriatic arthritis (PsA) may increase psychological burden in psoriasis, the mental health of this subpopulation is under‐investigated. Objectives To investigate whether PsA is associated with higher depression and anxiety in moderate‐to‐severe psoriasis; explore whether pain mediates these associations; and estimate the prevalence of undiagnosed and untreated depression. Methods Baseline data from British Association of Dermatologists Biologic and Immunomodulators Register (BADBIR) participants completing the Hospital Anxiety and Depression Scale (HADS) were analysed. Results 707 patients (n = 540 with psoriasis only; n = 167 with PsA) were included. Depression prevalence was higher in patients with than without PsA, when a HADS‐depression subscale cut‐off ≥8 was used (33% vs. 23%, adjusted Odds Ratio [OR] (95% Confidence Intervals [CI]) = 1.64 (1.09-2.45)), but did not differ using the HADS cut‐off ≥ 11. Anxiety prevalence was higher among PsA patients, regardless of HADS cut‐off (cut‐off ≥11: adjusted OR (95% CI) = 1.62 (1.07-2.45)). Pain fully mediated the effect of PsA on depression and anxiety in psoriasis. 53.6% of participants identified as depressed did not have a known psychiatric disorder; two thirds of depressed participants were not treated. Conclusions PsA comorbidity in psoriasis is associated with higher anxiety; its association with depression appears to be robust when milder depressive syndromes are included, but less consistent for higher‐threshold depression definitions. Depression remains unrecognized and untreated in over half of moderately‐to‐severe psoriasis patients. Routine depression and anxiety screening is recommended in psoriasis and PsA. PsA comorbidity may increase depression and anxiety in psoriasis through pain experience.